(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2023)
This paper is an exploratory study that aims to identify, describe, and compare the level of social capital on two types of cooperatives that have existed for a long time. The factors are determined by examining the structure of the organization and the members social capital. There were 120 respondents who were interviewed using the survey questionnaire to determine the members socio-demographic characteristics and ascertain the members level of social capital. A concurrent mixed method was used in the gathering and analysis of data. This study found that the member-respondents of the cooperatives have shown a high level of social capital in three dimensions: trust, norms, and reciprocity; networks and collective actions; and information and empowerment. However, the result of the T-test shows a significant difference between cooperatives in two dimensions: 1) trust, norms, and reciprocity, and 2) networks and collective actions. An examination of the profile of the organizations and their members revealed that the members ethnicity, religiosity, close family ties, and neighborliness may have contributed to a significant difference in these dimensions. Furthermore, the factors mentioned were found to impact how the cooperatives respond to, cope with, and mitigate threats, crises, and disasters. Furthermore, between cooperatives, better social capital is associated with better resiliency. This study recommends a more robust network affiliation with cooperatives in Bukidnon, Philippines and other cooperatives in the locale. It also recommends that the cooperatives may conduct routine risk assessments and create innovative ways to sustain the members social capital.